Healthcare Difficulties in the Post-GDPR Era - Alaya, Fátimah (Trinity Student Medical Journal, 2020)
The medical profession centres on the philosophy and principles of providing patients with the best evidence-based care. In doing so, medical clinicians must remain up-to-date with local and international best practice, engage in auditing practice to review and refine practices and engage in an open-relationship with the patient at the forefront of their practice. Protecting the patient encompasses best practice, moral and ethical principle while balancing risk and beneficence and ensuring non-maleficence, justice and patient autonomy. Alongside these aspects, comes the reality of advancing societal requirements which impact on medical practice and governance. The changing dynamic of patient consent that is required with the new General Data Protection Regulation (GDPR) requirements has changed the face of research in Ireland and Europe, with significant implications for research beyond as well. This piece will explore how healthcare data should be available for use for health research without the necessity to seek patient consent.